2020
DOI: 10.1364/ol.394171
|View full text |Cite
|
Sign up to set email alerts
|

High optical damage threshold on-chip lithium tantalate microdisk resonator

Abstract: Lithium tantalate (LT) is one of the most attractive optical nonlinear materials, as it possesses a high optical damage threshold and great UV transparency (0.28–5.5 µm). Recently, optical grade LT nanoscale film was developed. Here a high-quality-factor ( ∼ 10 5 ) LT microdisk resonator based on LT-on-insulator (LTOI) film is fabricated by utilizing focused ion beam (FIB) milling. 2 µW output second-harmonic waves are achieved in the LTOI microdisk at about 500 mW inpu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…However, the commercial use of LTOI in wireless applications, owing to its suitable acoustic properties, combined with the above optical properties, makes it an ideal platform for scalable manufactured electro-optical PICs, although such a use has never been demonstrated or pursued. Although free-standing ‘whispering gallery’ mode resonators have been fabricated from LiTaO 3 single crystals 26 , as a result of femtosecond laser direct writing 27 or focused ion beam milling 28 , scalable manufactured PICs have remained an outstanding challenge.…”
Section: Mainmentioning
confidence: 99%
“…However, the commercial use of LTOI in wireless applications, owing to its suitable acoustic properties, combined with the above optical properties, makes it an ideal platform for scalable manufactured electro-optical PICs, although such a use has never been demonstrated or pursued. Although free-standing ‘whispering gallery’ mode resonators have been fabricated from LiTaO 3 single crystals 26 , as a result of femtosecond laser direct writing 27 or focused ion beam milling 28 , scalable manufactured PICs have remained an outstanding challenge.…”
Section: Mainmentioning
confidence: 99%
“…Considering a relatively large nonlinear coefficient (d 33 ≈ 26 pm∕V), LT-on-insulator (LTOI) is another fascinating alternative for on-chip photonics who possesses a higher optical damage threshold (240 MW∕cm 2 ) and a greater UV transparency (0.28 to 5.5 μm), whereas there is little research in LTOI devices and their nonlinear characterization. 241 Fifth, laser-written waveguides may receive wider applications in the field of quantum photonics. Most recently, using a singlemode waveguide and a doughnut-shaped waveguide fabricated by femtosecond laser direct writing, Chen et al 48 demonstrated the vector vortex beam emitter carrying spin and orbital angular momentum mode inside a photonic chip, allowing for highdimensional quantum information processing.…”
Section: Summary and Perspectivesmentioning
confidence: 99%
“…At present, there are few studies on LTOI, and most of the researches are based on lithium tantalate bulk materials [28,29] . The LTOI features a higher laser-radiation-induced damage threshold [30] and a higher photorefractive damage threshold [31] . However, it is also notable that the second-order nonlinear coefficient d 33 of the LT is smaller than that of the LN, and in the case of uniaxial crystal, the properties of d eff can refer to Ref.…”
Section: Introductionmentioning
confidence: 99%